Cord blood bilirubin, albumin, and bilirubin /albumin ratio for predicting subsequent neonatal hyperbilirubinemia - Jehangir Allam Bhat; Sajad Ahmad Sheikh; Roshan Ara (Indonesian Pediatric Society, 2019)
Background Early discharge of healthy term newborns after delivery has become a common practice, because of medical and social reasons, as well as economic constraints. Thus, the recognition, follow-up, and early treatment of jaundice has become more difficult as a result of early discharge from the hospital. Since the dreaded complication of neonatal hyperbilirubinemia is kernicterus, an investigation which can predict the future onset of neonatal pathological jaundice is needed. Objective To investigate the predictability of neonatal hyperbilirubinemia by using cord blood bilirubin, albumin and bilirubin/albumin ratio. Methods This study was conducted on 300 healthy newborns. Umbilical cord blood was used to measure albumin and bilirubin. All infants were regularly followed up to 5th day of life. Neonates were divided into two groups: group A was consisted of neonates who developed jaundice which was in physiological range, while group B was consisted of neonates who developed neonatal hyperbilirubinemia (requiring phototherapy or other modality of treatment). Babies suspected to have bilirubin level which cross physiological limit on any day after birth were subjected to serum bilirubin measurement. Infants whose serum bilirubin level measurement revealed bilirubin levels crossing physiological values were sent to nursery for phototherapy. Results The incidence of neonatal hyperbilirubinemia was 11%. Statistically significant correlations between cord blood bilirubin, albumin, and bilirubin/albumin ratio to the development of neonatal hyperbilirubinemia were observed. On ROC analysis, cut-off points to predict significant hyperbilirubinemia in newborn were cord blood bilirubin >3 mg/dL (sensitivity 60.61%, specificity 97.63%), albumin <2.4 mg/dL (sensitivity 78.79%, specificity 98.13%), cord blood bilirubin/albumin ratio >0.98 (sensitivity 78.79%, specificity 95.51%). Conclusion Cord blood total bilirubin, albumin. and bilirubin/albumin ratio are excellent parameters to predict the occurrence of neonatal hyperbilirubinemia. However, cord blood albumin is better compared to cord blood bilirubin and bilirubin/albumin ratio.